LUGHAWI TAFSIR OF ḤĀSHIAH AL-ṢĀWI: A CRITICAL ANALYSIS OF TAFSĪR AL-JALĀLAIN - Rosihon Anwar (Qur’anic and Tafsir studies Programme at Ushuluddin Faculty, 2020)
Various approaches are employed by exegetes to understand the Qur’an. One of those approaches is the linguistic approach. One of tafsīr utilises the linguistic approach is Ḥāshiahal-Ṣāwī 'Alā Tafsīr al-Jalālain. This article investigates the characteristics and the unique attribution of Ḥāshiah al-Ṣāwī in its interpretation of the Qur’an, especially in the language rules usage through his examples in explaining the verses. This study employs a qualitative method to the data gathered from literature (library research) descriptively. The Data analysis technique used the Seidel model through several stages of the process, namely identifying the results of data collection through data clarification, license, analysis, and data categorization. This research shows that Ḥāshiah al-Ṣāwī 'Alā Tafsīr al-Jalālain is an essential and comprehensive interpretation using a linguistic approach. Al-Ṣāwī equipped his interpretation by explaining Nahwu (syntax), Ṣaraf (morphology), and the language rules application. He even quoting Alfiyyah Ibn Mālik, complete with its syi'ir which are very rare to do by other commentators to make his tafsīr more comprehensive. Several characteristics in Ḥāshiah al-Ṣāwī used a linguistic approach to the Qur’an utilizing the Arabic principle of mubtadi (basic), especially in the ‘Irāb (inflection) discussion. In this study, Ḥāshiah al-Ṣāwī 'Alā Tafsīr al-Jalālain can be categorized as an independent tafsīr that differ from tafsīr Al-Jalālain. Al-al-Ṣāwī not only explaining in detail tafsīr Jalalain but also criticizing and comparing it.